Antibacterial efficacy of pyrolysis-derived plant fractions against resistant pathogens: a comparative evaluation using nutrient and Müller-Hinton agar - Demirel, Maruf Hursit; Gul, Abdulkadir; Aydogmus, Ercan; Ozgen, Inanc; Arslanoglu, Hasan (Wiley, 2026)
BACKGROUND This study investigates the antibacterial potential of pyrolysis-derived extracts from rosehip fruit (RF), orange peel (OP), corn silk (CS), spurge root (ER) and mullein leaf (ML) against antibiotic-resistant pathogens using two different culture media. Bioactive compounds were obtained via a PID-controlled pyrolysis system, and antibacterial activity was evaluated to clarify both extract efficacy and medium-dependent effects on bacterial growth and diffusion.RESULTS Antibacterial activities were assessed using the agar well diffusion method, with ampicillin as a positive control, against Escherichia coli, Pseudomonas aeruginosa, Staphylococcus aureus and Enterococcus faecalis. A key novelty of this work is the comparative evaluation of extract performance on nutrient agar (NA) and M & uuml;ller-Hinton agar (MHA). Among all samples, the ML extract exhibited the strongest antibacterial activity across all tested strains, producing inhibition zones of 18.85 mm against E. coli and 17.15 mm against E. faecalis on NA, compared with 13.05 mm and 13.60 mm on MHA, respectively. CS and ER extracts showed moderate antibacterial effects, with consistently higher inhibition zones on NA than on MHA. Ampicillin generated substantially larger inhibition zones on NA (33.35 mm for E. coli and 34.45 mm for P. aeruginosa) compared with MHA (13.80 and 27.70 mm, respectively), confirming the strong influence of culture medium composition on measurable antibacterial activity.CONCLUSION These results indicate that both plant extracts and ampicillin exhibit higher antibacterial activity on NA than on MHA. The pronounced efficacy of the ML extract highlights pyrolysis-derived plant fractions as promising natural antimicrobials and emphasizes the critical importance of culture medium selection. (c) 2026 Society of Chemical Industry.
Keywords: antibiotic-resistant pathogens; antibacterial activity; bioactive compounds; nutrient agar; M & uuml;ller-Hinton agar; pyrolysis-derived extracts